STRATEGI PUBLIC RELATIONS DALAM MENANGANI KELUHAN PENUMPANG BANDARA INTERNATIONAL I GUSTI NGURAH RAI - larasati, kalih tasya; wedasari, putri (Universitas Pendidikan Nasional, 2017)
ABSTRACTResearch was conducted to describe the form of strategies used by public relations PT (PERSERO) Angkasa Pura I branch I Gusti Ngurah Rai International Airport in handling passenger complaints. Chossing I Gusti Ngurah Rai International Airport especially I Gusti Ngurah Rai International Airport is the busiest airport in Indonesia, Airport which is the main gate of entry and exit of foreign and domestic tourists to Bali , and because it is located on the Bali Island , that is tourism Island. This research uses type of qualitative descriptive research. Informants research selected accidental. Data collected through literature study, documentations, observation, depth interviews. Methods of data analysis using the data analysis model of Miles and Huberman. Technical examination of the validity data using triangulation techniques. Results of research show that public relations of PT (PERSERO) Angkasa Pura I branch I Gusti Ngurah Rai International Airport using strategy in handling passenger complaints by customer mobile, internal strategy, coordination strategy, and we care strategy. And strategies offered by Theory Image Restorations used by public relations PT (PERSERO) Angkasa Pura I branch I Gusti Ngurah Rai International Airport is mortification and corrective action strategies.Keywords: Public Relations Strategy and Passenger Complaints